Studies of the Properties of Sputtered CoAg and CoNiAg Granular Magnetic Thin Films - Abdullah, Huda (2002)
The observation of the magnetoresistance effect has been focussed on the studies of the giant magnetoresistance (GMR) effect, throughout the world, by researchers and scientists after its discovery from magnetic multilayer. It has later been observed in granular alloys in which nanometer-sized magnetic granules such as Co, Ni, Fe, are embedded in an immiscible metallic matrix (Ag, Cu, Au, etc.). These magnetic alloys having GMR effect find potential applications in magnetic field sensor and read heads. In this work, granular thin films of CoAg and CoNiAg alloys have been prepared using Radio frequency (RF) Magnetron sputtering technique. A split target composed of high purity (99.99%) Co, Ni and Ag metals have been bombarded with argon atoms to form plasma, which condensed onto the glass substrate to form thin films of various thicknesses depending on the deposition time and RF power. The characteristics and magnetotransport properties of GMR materials based on the CoAg and CoNiAg have been investigated. Magnetoresistance (MR) is usually expressed as the fractional change in resistance of a specimen produced by an applied field, GMR = MfR. For non-magnetic films MR is quite small, however the presence of magnetic entities in the non-magnetic matrix, increases its MR .and hence it is termed as GMR.